Wara’ dalam Ajaran Tasawuf Imam Junaid Al-Baghdadi - Abdul Hasib Asy'ari (Jurnal Penelitian Ilmu Ushuluddin, 2021)
The peak of Imam Junaid's Sufism is monotheism. One of the efforts to achieve this is the attitude of wara' by always emphasizing on self-awareness so as not to neglect the purpose of the search. This study uses a qualitative approach with data sources obtained from books, books and journals that examine wara', especially the views of Imam Junaid al-Baghdadi which aims to determineanalyze the teachings of al-Junaid aboutwara' in all aspects of life in order to avoid behaviors that can distance themselves from Allah Swt. This is needed because every individual Muslim should continue to protect himself from bad things and not fall into it. The results showed that wara'in the view of Al-Junaid has a close correlation with the intensity of one's awareness in controlling one's behavior in order to avoid things that can distance oneself from Allah Swt. It develops as far as the knowledge possessed, so that the more mature the knowledge and the intense in applying it, the higher the degree of one's sanity. So it can be concluded that wara' is based on awareness and knowledge to be aware of the behavior of the limbs from temptations that come from outside themselves.